2017
DOI: 10.1021/acs.jmedchem.7b00952
|View full text |Cite
|
Sign up to set email alerts
|

Stilbene Boronic Acids Form a Covalent Bond with Human Transthyretin and Inhibit Its Aggregation

Abstract: Transthyretin (TTR) is a homotetrameric protein. Its dissociation into monomers leads to the formation of fibrils that underlie human amyloidogenic diseases. The binding of small molecules to the thyroxin-binding sites in TTR stabilizes the homotetramer and attenuates TTR amyloidosis. Herein, we report on boronic acid-substituted stilbenes that limit TTR amyloidosis in vitro. Assays of affinity for TTR and inhibition of its tendency to form fibrils were coupled with X-ray crystallographic analysis of nine TTR·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 85 publications
(208 reference statements)
0
24
0
Order By: Relevance
“…To investigate BOL in this context, we designed and synthesized stilbene 1. This compound resembles ligands that are known to bind to the tetrameric form of human transthyretin and thereby deter its aggregation into fibrils that underlie human amyloidogenic diseases (53,54). We found that stilbene 1 attenuates the formation of transthyretin fibrils in a concentration-dependent manner (SI Appendix, Table S14).…”
Section: Scope Of the Resistance To Oxidation Of Boronic Acid-carboxymentioning
confidence: 82%
See 1 more Smart Citation
“…To investigate BOL in this context, we designed and synthesized stilbene 1. This compound resembles ligands that are known to bind to the tetrameric form of human transthyretin and thereby deter its aggregation into fibrils that underlie human amyloidogenic diseases (53,54). We found that stilbene 1 attenuates the formation of transthyretin fibrils in a concentration-dependent manner (SI Appendix, Table S14).…”
Section: Scope Of the Resistance To Oxidation Of Boronic Acid-carboxymentioning
confidence: 82%
“…Supporting Information. Human transthyretin was produced with recombinant DNA technology in Escherichia coli as described previously(54). Phosphate-buffered saline (PBS) was made with ingredients from Research Products International and contained (in 1.0 L): 0.2 g KCl, 0.2 g KH2PO4, 8 g NaCl, and 2.16 g Na2HPO4•7H2O at pH 7.3.NMR spectra were obtained with an Avance-400, Avance-500, or Avance-600 spectrometer from Bruker.…”
mentioning
confidence: 99%
“…Additional restraints were imposed to provide accurate bond distances and angles, as described previously (54). Fig.…”
Section: Inhibition Of Fibril Formation Transthyretin Fibril Formatimentioning
confidence: 99%
“…The unique catalytic environment of enzymes or binding proteins offers vastly diverse covalent reactions, including acylation, 1,4‐Michael addition, alkylation, carbamylation, and boronation etc [8–10] . These covalent reactions allow us to develop covalent probes targeting folded proteins, including fluorescent probes for bio‐imaging, covalent drugs for therapeutic purposes, [11–16] and activity based probes for chemical proteomics [17–24] etc. Besides these naturally existing chemical reactivity, introduction of unnatural amino acids enormously broadens the horizon of chemical reactivity and enriches the bioorthogonal chemistry toolbox for selective bioconjugation and functionalization of folded proteins [25–28] …”
Section: Introductionmentioning
confidence: 99%